Reactions of Law Enforcement to LGBTQ Diversity Training. (5th April 2017) - Israel, Tania; Bettergarcia, Jay N.; Delucio, Kevin; Avellar, Todd Raymond; Harkness, Audrey; Goodman, Joshua A.
Abstract : Knowledge about the ways in which employees respond to workplace diversity training can help in the preparation and delivery of the training. Few studies have looked at responses toward with lesbian, gay, bisexual, transgender, and queer (LGBTQ) diversity training, in general, or with law enforcement, in particular. The present study examined reactions, specifically resistance and receptiveness, to an LGBTQ diversity training for approximately 120 law enforcement officers. Twenty subthemes about resistance were categorized into four overarching themes: perceptions of law enforcement, beliefs regarding LGBTQ community, defending law enforcement practices, and nonverbal forms of resistance. Seventeen subthemes about receptiveness were organized into five main themes: requesting elaboration from trainers, how law enforcement can support LGBTQ people, awareness and motivation to address LGBTQ community needs, appreciation for the training, and helping the trainers or training succeed. The results indicate that both resistance and receptiveness were present among participants. Further, some of the receptiveness and resistance is similar to what is found in the literature, while some of these reactions were unique to LGBTQ diversity training and working with law enforcement.